Los nuevos abogados : una lectura de las representaciones institucionales desde los discursos de colación de grados - Cardinaux, Nancy (2012)
This work is aimed at presenting some results of an investigation made on the corpus of the speeches delivered during the last seven years by the University of Buenos Aires Law School professors in degree ceremonies, applying the technique of speech analysis. By applying a technique that combines quantitative and qualitative criteria to all speeches, we have analyzed a series of topics related to their content, taking into account the pragmatic dimension. The object of study is highly formalized speeches that can be seen in some institutional representations. From important common points, we intend to determine the speakers' representations on the School graduates, and also on the ethical rules governing the legal profession.